MANAJEMEN KONFLIK DALAM PENGELOLAAN KELAS SEBAGAI STRATEGI UNTUK MENINGKATKAN KEBERHASILAN PEMBELAJARAN - M. Multazami; Ayu Dwi Mashlihah; M. Naufal Ifkaruddin; Imam Syafi’i; Saefullah Azhari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe conflict management in classroom management as a strategy to improve learning success. Through a qualitative approach and literature review method, this study analyzes various reference sources, including books, journals, and previous studies. The results of the study indicate that effective conflict management requires strategies such as early conflict prevention, identification of conflict sources, constructive conflict resolution, and follow-up evaluation. However, the implementation of this strategy faces internal and external obstacles. The conclusion is that good conflict management can create a conducive learning environment and improve learning success. Therefore, improving teacher competence in communication, negotiation, and emotional management, as well as support from educational policies and parental participation, are key factors in managing conflict in the classroom.